Fast and direct determination of fragility in metallic glasses using chip calorimetry. Issue 3 (March 2019) - Spieckermann, Florian; Steffny, Innozenz; Bian, Xilei; Ketov, Sergey; Stoica, Mihai; Eckert, Jürgen
Abstract: We directly determine the thermodynamic fragility index of two metallic glasses (Mg65 Cu25 Gd10 and Au49 Cu26.9 Si16.3 Ag5.5 Pd2.3 ) from fictive temperature shifts induced by a variation of the quenching rate using fast differential scanning calorimetry (FDSC). Recent chip calorimeters are able to achieve the cooling rates necessary to perform such an evaluation. For the Mg65 Cu25 Gd10 and Au49 Cu26.9 Si16.3 Ag5.5 Pd2.3 metallic glasses studied, we find very good agreement of the kinetic fragility index with literature data obtained by conventional calorimetry and rheology. The thermodynamic fragility indices are m=25.5 ± 1.5 for Mg65 Cu25 Gd10 and m=50.3 ± 2.3 for Au49 Cu26.9 Si16.3 Ag5.5 Pd2.3, respectively. The FDSC method discussed here allows for fast and reliable determination of the kinetic fragility of metallic glasses, and is thus competitive with high-frequency methods.